Photoswitchable Sol–Gel Transitions and Catalysis Mediated by Polymer Networks with Coumarin‐Decorated Cu24L24 Metal–Organic Cages as Junctions. Issue 7 (16th January 2020) - Oldenhuis, Nathan J.; Qin, K. Peter; Wang, Shu; Ye, Hong‐Zhou; Alt, Eric A.; Willard, Adam P.; Van Voorhis, Troy; Craig, Stephen L.; Johnson, Jeremiah A.
Abstract: Photoresponsive materials that change in response to light have been studied for a range of applications. These materials are often metastable during irradiation, returning to their pre‐irradiated state after removal of the light source. Herein, we report a polymer gel comprising poly(ethylene glycol) star polymers linked by Cu24 L24 metal–organic cages/polyhedra (MOCs) with coumarin ligands. In the presence of UV light, a photosensitizer, and a hydrogen donor, this "polyMOC" material can be reversibly switched between Cu II, Cu I, and Cu 0 . The instability of the MOC junctions in the Cu I and Cu 0 states leads to network disassembly, forming Cu I /Cu 0 solutions, respectively, that are stable until re‐oxidation to Cu II and supramolecular gelation. This reversible disassembly of the polyMOC network can occur in the presence of a fixed covalent second network generated in situ by copper‐catalyzed azide‐alkyne cycloaddition (CuAAC), providing interpenetrating supramolecular and covalent networks. Abstract : Supramolecular polymer metal–organic cage (polyMOC) gels with Cu24 L24 cuboctahedral junctions featuring a high density of coumarin ligands were prepared. These robust, dynamic materials could be reversibly switched between Cu II, Cu I, and Cu 0 states, each with distinct mechanical, optical, and catalytic properties. In particular, the Cu I state was used to catalyze covalent network formation, providing novel polyMOC covalent double networks.